Dulcie and Dud and the really dumb play - Martin, Ann, 1942-; Dawson, Janine (Norwood, S. Aust. : An Omnibus Book from Scholastic Australia, 2002)
"Mrs Besome thinks her play is fantastic. Stuck-up Portia Pratt does too - she's got the biggest, best part. But Dulcie and her friend Dud think this is a really dumb play. And they're going to show Mrs Besome what a really good play is all about."
For children aged 6-9 years.
Keywords: Children's plays -- Juvenile fiction; Amateur plays -- Juvenile fiction